Resource Description and Access (RDA): conceitos e relações da RDA Original e do Projeto 3R - Cavalheiro, Karen Cristina Soares (2022)
With the emergence of technologies and the Web, the processes, methodologies and instruments of Information Organization began to undergo transformations, and have been continuously developed for an Information Representation that fits the current digital environments. One of the instruments most used by the library community internationally is the Anglo-American Cataloguing Rules (AACR2r). This code was not developed with the intention of representing informational resources in digital and Web environments. Thus, in its latest revised version, the study group responsible for the reviews decided to develop a set of guidelines for resource description and access, the Resource Description and Access (RDA). The RDA was developed by the RDA Steering Committee (RSC) as a set of data elements, or guidelines and instructions for creating metadata for library and cultural heritage resources. These guidelines seek to promote agility, ease, optimization, and better use of the work of Information Science professionals, allowing adaptations to suit different types of libraries and for different user communities. In 2017, the IFLA-LRM conceptual model was published, with the aim of unifying the FRBR, FRAD, FRSAD models, consolidating a single structure as the reference model for libraries. In this context, there is an intensification of the use of Semantic Web technologies, such as Linked Data, which presented a new perspective for description and data linking. With these changes, the RDA Steering Committee group verified the need for a new structure of the RDA, published in June 2022 called 3R Project. This project reformulated the structure of the RDA and aligned with the proposal of the IFLA-LRM. Given this scenario, it was observed that many changes were necessary to adapt the RDA to the IFLA-LRM. That said, the guiding question of this research was: what are the main changes in the RDA with the 3R Project? And what might be the impacts of these changes? Thus, the general objective of this research was to present the changes in the RDA considering the changes developed in the 3R Project. The specific objectives were: to conceptualize the structure and history of the RDA and the 3R Project; Verify the use of the RIMMF as a demonstrative tool for resource cataloging in the context of the RDA (original and 3R Project) and present records using the guidelines before and after the 3R Project. The research is characterized as exploratory and descriptive, of a theoretical and qualitative nature. The comparative method was used to analyze the results obtained with the RIMMF 3.0, 4.0 and RDA Toolkit tools. This new perspective based on cataloging in RDA significantly changed the presentation of data, which before in AACR2r was much more focused on adapting to the dimensions of the cataloging file. The emergence of conceptual models impacted on the creations and updates of the RDA. Since then, these publications have presented a new perspective for cataloging. To contemplate the first objective, the concepts, structure and history of the Original RDA and the 3R Project were presented, for the other objectives, the records using the RDA and the 3R Project were presented. It is concluded that the RDA Project 3R caused changes in the RDA Toolkit, in the structure of the RDA guidelines and promoted approximations with the IFLA-LRM and with the Linked data context. Major changes have been made structurally to the RDA so that the IFLA-LRM conceptual model is in line with the current cataloging processes that encompass the RDA.